Taxonomic studies on two Interesting species of Auricularia (Wood Ear Mushroom) from Arunachal Pradesh, India - Parihar, Arvind; Ghosh, Arijit (Mushroom Research, 2025)
Auricularia, a genus of macrofungi with broad geographical distribution, is highly valued for its edible and medicinal properties. It ranks as the third most extensively cultivated mushroom worldwide due to its remarkable nutritional and bioactive attributes. This article provides detailed descriptions and colour illustrations of two notable Auricularia species. Specifically, Auricularia australica has been newly documented for the Indian mycobiota.